Probiotic fermentation enhances the antihypertensive activity of Astragali radix via redox-inflammation-endothelial interaction axis - Yue-Yue Liu; Zhen-Hui Pan; Ya-Li Zhao; Teng-Gen Hu; Hong Wu (Food Bioscience, 2026)

Improvement of surface hydrophilicity by nanometer oxides to promote aluminum-water reaction to generate hydrogen - Gen-Wang Ma; Xiao-Han Guo; Wei-Zhuo Gai; Yang Yang; Jie Zhang; Zheng-hui Pan; Zhen-Yan Deng (Fuel, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

A robust bi-objective optimization model and heuristic solution for truck-drone collaboration in humanitarian logistics under truck travel time uncertainty - Huizhen Zhang; Chaoyue Pan; Mitsuo Gen (Swarm and Evolutionary Computation, 2026)

Heat Stress Induces Cognitive Impairment Through ACSL4-Mediated Lipid Peroxidation and Subsequent Ferroptosis - Qicheng Zhou; Xinyao Liu; Wenlan Pan; Yicui Qu; Wenjing Shi; Gen Miao; Lu Huang; Xin Li; Mengyu Cai; Hongxia Li; Hui Shen (Molecular Neurobiology, 2026)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Enhanced catalytic decomposition of methyl formate to carbon monoxide and methanol using palladium/activated carbon catalyst: Mechanistic insights and catalyst design considerations - Wei Shen; Xin Zhang; Yuanyuan Huang; Liyuan Xu; Ran Wang; Wenxing Yang; Pengbin Pan; Yuan-Gen Yao (Fuel, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Molecular mapping of QTL for rice black-streaked dwarf disease resistance in rice (Oryza sativa L.) - Zhiguang Sun; Gen Pan; Hongzhou An; Baoxiang Wang; Dayong Xu (Cereal Research Communications, 2024)
Rice black-streaked dwarf disease (RBSDD) is one of the most serious crop diseases in Asia, causing serious damage to rice production. Therefore, reducing the harmful effects of RBSDD is vital to the food security of China and other Asian countries. In this study, 248 rice varieties from different countries were screened for resistance to RBSDD, and 19 varieties with high resistance to RBSDD were found. Among them, H185, an indica variety, showed stable and high resistance to RBSDD. Using an F 2:3 population of H185 and Wuyujing 3 (WYJ3, a highly susceptible japonica rice variety), three QTL conferring resistance to RBSDD, namely qRBSDD2 , qRBSDD7 , and qRBSDD11 were identified, and they explained 53.6% of the total phenotypic variation. Among them, qRBSDD2 and qRBSDD7 , with LOD scores of 4.26 and 4.25, respectively, were repeatedly detected in artificial inoculation conditions, accounting for 28.0% and 29.8% of the total phenotypic variation, respectively. Resistant alleles of the two QTL were all derived from H185, and several BC 5 F 2 lines possessing single or two QTL of qRBSDD2 and qRBSDD7 exhibited higher resistance for RBSDD. The QTL detected in our study open new possibilities for breeding rice cultivars with RBSDD resistance through resistance gene pyramiding.

Significant contribution of carbonyls to atmospheric oxidation capacity (AOC) during the winter haze pollution over North China Plain - Xue Yang; Gen Zhang; Guang Pan; Guolan Fan; Houyong Zhang; Xuan Ge; Mingyue Du (Journal of Environmental Sciences, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

OsFKBP42b Regulates Rice Growth and Development Through Interacting with OsABCB1 and OsABCB14 - Di Wang; Yingjie Wang; Gen Pan; Yanyan Wang; Guizhi Wang; Wenjing Chen; Yating Feng; Xi Liu (Journal of Plant Biology, 2023)

Protective effects of egg yolk immunoglobulins (IgY) against CyHV-2 infection in gibel carp (Carassius gibelio) - Bing-Yao Sun; Hai-Yan Kou; Pan-Yang Jian; Ling-Jiao Kong; Jie Fang; Peng-Kun Meng; Kang Wu; Cai-Gen Yang; Gang Yang; Xue-Hong Song (Aquaculture, 2023)

Neuroprotective effect of hyperoside in MPP+/MPTP -induced dopaminergic neurodegeneration - Xing-Jie Xu; Tao Pan; Hui-Jie Fan; Xu Wang; Jie-Zhong Yu; Hai-Fei Zhang; Bao-Guo Xiao; Zhen-Yu Li; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

High-resolution genetic map construction and QTL analysis of important fiber traits in kenaf using RAD-seq - Li Hui; Chang Li; Tang Huijuan; Luan Mingbao; Pan Gen; Huang Siqi; Jiang Hui; Wu Yena; Chen Anguo (South African Journal of Botany, 2023)

Feasibility analyses of virtual models and 3D printing for surgical simulation of the double-outlet right ventricle - Jixiang Liang; Bingheng Lu; Xin Zhao; Jiong Wang; Dianjiang Zhao; Gen Zhang; Bin Zhu; Qiang Ma; Guangyu Pan; Dianyuan Li (Medical & Biological Engineering & Computing, 2022)

Development and application of novel InDel markers in flax (Linum usitatissimum L.) through whole-genome re-sequencing - Hui Jiang; Gen Pan; Touming Liu; Li Chang; Siqi Huang; Huijuan Tang; Yuan Guo; Yena Wu; Jie Tao; Anguo Chen (Genetic Resources and Crop Evolution, 2022)

Genome-wide association analysis of fiber fineness and yield in ramie (Boehmeria nivea) using SLAF-seq - Kunyong Huang; Yaliang Shi; Gen Pan; Yicheng Zhong; Zhimin Sun; Juan Niu; Jing Chen; Jianhua Chen; Mingbao Luan (Euphytica, 2021)

Physiological responses and tolerance of flax (Linum usitatissimum L.) to lead stress - Gen Pan; Lining Zhao; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Zhigang Dai; Anguo Chen; Defang Li; Zheng Li; Yong Deng (Acta Physiologiae Plantarum, 2020)

Cleaning chromium pollution in aquatic environments by bioremediation, photocatalytic remediation, electrochemical remediation and coupled remediation systems - Caiwen He; Lipeng Gu; Zhixiang Xu; Huan He; Gen Fu; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Chemistry Letters, 2020)

Genome-wide development of simple sequence repeats database for flax (Linum usitatissimum L.) and its use for genetic diversity assessment - Gen Pan; Anguo Chen; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Lining Zhao; Defang Li (Genetic Resources and Crop Evolution, 2020)

Effects of micrite microtextures on the elastic and petrophysical properties of carbonate reservoirs - Jian-Guo Pan; Ji-Xin Deng; Chuang Li; Hong-Bin Wang; Hu-Quan Zhang; Jian-Guo Zhao; Gen-Yang Tang (Applied Geophysics, 2019)

Estimating multi-frequency satellite phase biases of BeiDou using maximal decorrelated linear ambiguity combinations - Gen Liu; Xiaohong Zhang; Pan Li (GPS Solutions, 2019)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Dynamic patterns of histone H3 lysine 4 methyltransferases and demethylases during mouse preimplantation development - Gen-Bao Shao; Jun-Chao Chen; Liu-Ping Zhang; Pan Huang; Hong-Yan Lu; Jie Jin; Ai-Hua Gong; Jian-Rong Sang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Evaluation of M307 of FUT1 gene as a genetic marker for disease resistance breeding of sutai pigs - Wen-bin Bao; Lan Ye; Jing Zhu; Zhang-yuan Pan; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

Erratum to: The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

Beneficial genotype of swine FUT1 gene governing resistance to E. coli F18 is associated with important economic traits - WEN-BIN BAO; LAN YE; ZHANG-YUAN Pan; JIN ZHU; GUO-QIANG ZHU; XUE-GEN HUANG; SHENG-LONG WU (Journal of Genetics, 2011)

Aortoduodenal fistula following aortic reconstruction of a pseudoaneurysm caused by stab wound 12 years ago - Jian-cang Zhou; Qiu-ping Xu; Lai-gen Shen; Kong-han Pan; Yi-ping Mou (Journal of Zhejiang University-SCIENCE B, 2009)

Heavy metal accumulation from zinc smelters in a carbonate rock region in Hezhang County, Guizhou Province, China - Yuan-Gen Yang; Cong-Qiang Liu; Wu Pan; Guo-Ping Zhang; Wei-Huang Zhu (Water, Air, & Soil Pollution, 2006)

Web GIS: Implementation issues - Kou-gen Zheng; Soomro Tariq Rahim; Yun-he Pan (Chinese Geographical Science, 2000)